The Impact of Organizational Innovation Climate on Sustainable Competitive Advantage- Empirical Study - Saleh Hassan, Ibrahim; Mohammed Ismael, Firas (Journal of Economics and Administrative Sciences, 2023)
The problem of the research is that some companies lack the mechanisms and policies that to enhance the loyalty of these valuable resources, which led to difficulties in generating knowledge, producing, storing, investing and investing information to achieve a sustainable competitive advantage. In addition, companies are still working with the traditional wage system (monthly salaries), which makes people not think about adding value to work. The research aims to determine the level of variables for researchers to clarify the impact of the organizational innovation climate on sustainable competitive advantage. The Qualitative approach is used based on research. The research was applied in Internet Companies (Earth Link, Al-Hayat, Al-Jazeera, Hala Al-Rafidain, Orient, Sobriel, and Dish Net) in the city of Baghdad. A sample of (167) individuals in the aforementioned companies was chosen, relying on the methodology of this research, which is the survey methodology that relies on analyzing the questionnaire based on theoretical hypotheses that have been proven through practical tests and comparing the results between them.The research finds that dimensions are available regarding the climate of organizational innovation and sustainable competitive advantage. The results show that there is an impact of the organizational innovation climate on the sustainable competitive advantagePaper type: Research paper